Effectiveness of CFRP seismic-retrofit of circular RC bridge piers under vehicular lateral impact loading. (15th September 2021) - Zhou, S.C.; Demartino, C.; Xu, J.J.; Xiao, Y.
Highlights: Lateral static and impact behavior of propped cantilever columns was investigated. The effectiveness of CFRP seismic-retrofit under impact has been experimentally investigated. A comparison of the lateral impact and static behavior of RC columns is reported. A semi-empirical equation is proposed to estimate the dynamic response given the static behavior. CFRP seismic-retrofit is effective in reducing damage under vehicular lateral impact loads. Abstract: The effectiveness of Carbon Fiber Reinforced Polymer (CFRP) seismic-retrofit of circular Reinforced Concrete (RC) bridge piers under vehicular lateral impact loading is addressed in the present work performing experimental tests. Sixteen 1 / 3 scale RC bridge piers with circular cross-sections characterized by three different configurations of longitudinal and transverse reinforcements were tested with and without CFRP seismic-retrofit. In the first case, tested columns represent common shear-deficient RC bridge piers designed with obsolete design practice or for non-seismic areas. In the second case, CFRP wrapping is applied according to common seismic-retrofit practices to increase the shear capacity and ductility of columns. Experimental tests were carried out under static and lateral impact loading with propped cantilever conditions reproducing a typical short-span viaduct bridge pier configuration. In the static tests, the lateral load was applied monotonically through a hydraulic jacket under equivalent impact conditions. In impact tests, the lateral impact load was applied through a colliding truck equipped with a rigid hammer at the typical vehicular impact location adopting two different impact velocities (3 and 4.5 m / s ). A critical investigation of the transient dynamic characteristics, damage evolution, and post-impact damage is conducted by comparing the results obtained with and without CFRP seismic-retrofit, and under static and dynamic loading conditions. It is shown that CFRP seismic-retrofitting of circular RC bridge pier can also be effective in reducing the vulnerability under lateral impact loading. The CFRP-retrofit approach adopted in this study meets the requirement of multi-hazard prevention improving the robustness of the bridge. Finally, a semi-empirical equation for predicting the maximum displacement under impact loading is derived based on experimental results. The proposed equation adopts the results of a static test as a proxy for assessing the dynamic behavior allowing for the design of the required shear and flexural load-carrying capacity.